Impacts of ridge–furrow rainfall concentration systems and mulches on corn growth and yield in the semiarid region of China. (3rd February 2016) - Ren, Xiao‐Long; Zhang, Peng; Chen, Xiao‐Li; Jia, Zhi‐Kuan
Abstract: BACKGROUND: Plastic‐covered ridge–furrow farming systems for rainfall concentration (RC) improve the water availability for crops and increase the water use efficiency (WUE), thereby stabilizing high yields. In this study, we optimized the mulching patterns for RC planting to mitigate the risks of drought during crop production in semiarid agricultural areas. We conducted a 4‐year field study to determine the RC effects on corn production of mulching in furrows with 8% biodegradable films (RCSB ), liquid film (RCSL ), bare furrow (RCSN ) and conventional flat (CF) farming. RESULTS: We found that RC significantly ( P > 0.05) increased the soil moisture in the top 0–100 cm layer and the topsoil temperature (0–20 cm) during the corn‐growing period. Mulching with different materials in planting furrows further improved the rain‐harvesting, moisture‐retaining and yield‐increasing effects of RC planting. Compared with CF, the 4‐year average total dry matter amount per plant for RCSB, RCSL and RCSN treatments increased by 42.1%, 30.8% and 17.2%, respectively. The grain yield increased by 59.7%, 53.4% and 32.6%, respectively. CONCLUSION: Plastic‐covered ridge and furrow mulched with biodegradable film and liquid film is recommended for use in the semiarid Loess Plateau of China to alleviate the effects of drought on crop production. © 2015 Society of Chemical Industry